More than a sex crime: a feminist political economy of the 2014 iCloud hack. (January 2022) - Patrick, Stephanie
This article examines the media framing of and relations to the 2014 iCloud hack, wherein hundreds of female celebrities' private photos were stolen and distributed online. In particular, I problematize the reading of this event as merely signalling the misogyny of 'toxic' online cultures and contextualize it as part of a larger political economy of female celebrity. I argue that, while the growth in feminist discourses emanating from both the mainstream media and celebrity women is encouraging, it perhaps occludes the broader power relations that extend across both new and traditional media, ensuring maintenance of the status quo. This event exemplifies problems with a popular form of feminism that seeks inclusion into these systems, rather than wider systemic change. Therefore, in addition to examining the celebrity and/or her audience as the site of political (feminist) work, I call for an excavation of the systems in which she is embedded and her relations to the means of media production and profit.